Analisis Dampak FLEGT VPA Terhadap Ekspor Hutan Indonesia Ditengah EU Green Deal - Hino Samuel Jose (Cendekia Niaga, 2021)
Forestry export is one of Indonesia’s strongest industries embraced in economic diplomacy or the international trade negotiation. FLEGT VPA that is conducted between Indonesia and European Union gave a fresh head start for Indonesia’s forestry exports, however it also exposed Indonesia into new challenges amid the Indonesia-EU CEPA negotiation with the EU Green Deal happening. Therefore, Indonesia needs to scrutinize every dimension that might obstruct national export development in the post-pandemic era and to keep the demands flowing for the forest industries. This article is aimed to discuss on how FLEGT VPA impacts Indonesia’s forest timber exports after the signing of Permendag 74/2020. This article also discussed the context on how Indonesia through FLEGT VPA can face against the EU Green Deal in forestry export. This article is researched using document-based research of literature studies and supporting data. This research concludes that FLEGT VPA through Permendag 74/2020 is adopted as part of Indonesia’s trade development and recovery efforts in post Covid-19 pandemic and to adopts the Timber Legal Verification System. FLEGT VPA has also impacts the forestry small and medium exporters because of the increased production cost as the result of the timber bureaucracy that was set by the government. This article resulted that FLEGT VPA however imposed challenges but at the same time developing its market capabilites and export to create a positive image for the sustainable timber industry. Amid the increased green politics in European Union affecs intra ASEAN hence committed for all member states in starting through possible foreign trade and economic cooperation scheme.